Diffuse large B‐cell lymphoma of the ocular adnexal region: A nation‐based study. (2nd May 2012) - Rasmussen, Peter K.; Ralfkiaer, Elisabeth; Prause, Jan U.; Sjö, Lene D.; Toft, Peter B.; Siersma, Volkert D.; Heegaard, Steffen
Abstract. Purpose: To characterize the clinicopathological features of diffuse large B‐cell lymphoma (DLBCL) of the ocular adnexal region. Methods: The present series of orbital and adnexal DLBCLs were found by searching the Danish Registry of Pathology between 1980 and 2009. Histological specimens were re‐evaluated using a panel of monoclonal antibodies. Clinical files from all patients with confirmed DLBCL were collected. Results: A total of 34 patients with DLBCL of the ocular adnexal region were identified. Eighteen of the patients were men. The patients had a median age of 78 years (range 35–97 years). Ninety‐seven per cent of the patients had unilateral ocular adnexal region involvement, and the orbit (76%) was the most frequently affected site. Nineteen patients (56%) presented with Stage I lymphoma. Of these, 18 were diagnosed with primary lymphoma. Four patients (12%) had Stage II, one patient (3%) had Stage III and ten patients (29%) presented with Stage IV lymphoma. The 5‐year overall survival (OS) rate for the whole study group was 20%. The patients with Stage I lymphoma had a significantly better 5‐year OS rate (28%) than patients in Stage II‐IV (5‐year OS rate, 9%). In Cox regression analysis, concordant bone marrow involvement and the International Prognostic Index (IPI) score were prognostic factors for OS. Conclusions: Diffuse large B‐cell lymphoma of the ocular adnexal region is mainly prevalent in elderly patients. Most patients had unilateral orbital involvement. The overall prognosis is poor. Concordant bone marrow involvement and the IPI score were independent prognostic factors for mortality.